3D Hierarchical nano-flake/micro-flower iron fluoride with hydration water induced tunnels for secondary lithium battery cathodes. (February 2017) - Bai, Ying; Zhou, Xingzhen; Zhan, Chun; Ma, Lu; Yuan, Yifei; Wu, Chuan; Chen, Mizi; Chen, Guanghai; Ni, Qiao; Wu, Feng; Shahbazian-Yassar, Reza; Wu, Tianpin; et al.
Abstract: As a potential multi-electron electrode material for next generation lithium ion batteries, iron fluoride (FeF3 ) and its analogues are attracting much more attentions. Their microstructures are the key to achieve good electrochemical performances. In this work, FeF3 ·3H2 O nano-flakes precursor with high crystallinity and flower-like morphology is synthesized successfully, by a liquid precipitation method using Fe(NO3 )3 ·9H2 O and NH4 HF2 as raw materials. The formation and the crystal growth mechanisms of the FeF3 ·3H2 O precursors are investigated and discussed. After different temperature heat-treatment and followed by ball-milling with Super P, the as-prepared FeF3 .0·33H2 O/C and FeF3 /C nanocomposites are used as cathode materials for lithium ion batteries. The FeF3 .0·33H2 O/C nanocomposite exhibits a noticeable initial specific capacity of 187.1 mAh g −1 and reversible specific capacity of 172.3 mAh g −1 at .1 C within a potential range of 2.0–4.5 V. The capacity retention is as high as 97.33% after 50 cycles. Combined with HRTEM test, it confirms that the hydration water is not harmful but useful, namely, the tunnel phase formed with the hydration water is crucial to unobstructed Li + diffusion, and therefore leading to excellent electrochemical performances. Graphical abstract: FeF3 ·3H2 O nano-flakes precursor with high crystalline degree and beautiful flower-like morphology is synthesized successfully by liquid precipitation method and the self-assembling mechanisms are investigated and discussed. Subsequently-prepared FeF3 .0·33H2 O/C and FeF3 /C nanocomposites are used as cathode materials for lithium ion batteries. Hydration water is proven to play an crucial role in the structure and electrochemical performances of the iron fluoride. Highlights: Iron fluoride nano-flakes precursor with flower-like morphology is synthesized. Self-assembling mechanisms of iron fluoride nano-flakes are illustrated and discussed. Iron fluoride nanocomposite achieves a high reversible capacity of 172.3 mAh g −1 . The capacity retention is as high as 97.33% after 50 cycles. The effects of hydration water on the electrochemical properties are made certain.